Identifikasi Potensi Ciri-ciri Wirausaha Dengan Model Anggadiredja dan Djajamihardja Pada Mahasiswa Universitas Gunung Rinjani - Siti Reuni Inayati; Lalu Rizal Ihwandi (Universitas Hamzanwadi, 2020)
This study aims to determine how high the potential for entrepreneurial characteristics of Gunung Rinjani University students using the Anggadiredja and Djajamihardja models. This type of research is a quantitative research which is descriptive statistics. Data were collected using a questionnaire with a total of 150 respondents. There are 4 stages in this research, in the first stage making a list of 96 statements regarding 12 characteristics of entrepreneurship according to Anggadiredja and Djajamihardja (1991). The second stage, respondents simply answer or provide an opinion on the 96 statements in the table. Furthermore, the third and fourth stages, namely the assessment of entrepreneurial characteristics and knowing the potential level of respondents using descriptive analysis. Research results show that, Based on the results of the questionnaire from 150 respondents, the average value for the first characteristic is 24.7, the second characteristic is 24.6, the third characteristic is 24.7, the fourth feature is the average value is 24.7. 25.4, the fifth feature has an average value of 25.37, the sixth feature has an average value of 25.5, the seventh characteristic has an average value of 24.75, the eighth characteristic is obtained an average value of 24.6, the ninth feature has an average value -the average value is 24.2, the average value of the ten characteristics is 24.45, the average value of the eleventh characteristic is 25.1 and the average value of the twelfth feature is 25.1. So it can be concluded that the potential for entrepreneurial characteristics of each respondent is in the medium category because it has a value range between 17-31